Analysis Of The Effect Of Guardrail Type On Road Crash Fatality In Indonesia - Sodikin Usman; Dzikrul Kusnul Hadi (Politeknik Transportasi Darat Indonesia - STTD Bekasi, 2025)
Road traffic fatalities in Indonesia remain a critical public health and transportation challenge, with roadside barrier performance being an underexplored factor in injury severity outcomes. This study examines the relationship between guardrail type and crash fatality risk using a binary logistic regression model. Secondary data from 30 crash events involving guardrail collisions were sourced from investigation reports issued by the National Transportation Safety Committee (KNKT) spanning 2007–2023. Crash outcomes were classified as fatal or non-fatal, while guardrail systems were categorized as rigid or semi-rigid. Logistic regression results yielded an odds ratio of 1.99 for rigid guardrails, indicating that crashes involving rigid barriers carry nearly twice the probability of a fatal outcome compared to semi-rigid systems. Estimated fatality probability was 44.6% for rigid guardrails and 28.8% for semi-rigid guardrails. Risk reduction analysis demonstrated that semi-rigid barriers reduce relative fatality risk by 35.4%, with an absolute risk reduction of 15.8% and a Number Needed to Treat (NNT) of 6. These findings provide quantitative evidence that semi-rigid guardrail systems, through their energy-absorbing deformation capacity, are more consistent with forgiving road design principles. The results establish a technical foundation for evidence-based infrastructure investment and policy decisions aimed at reducing road traffic fatalities in Indonesia.